(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study investigates the physicochemical parameters of Sathnala Pond in Adilabad District, Telangana, to evaluate its water quality and ecological health across different seasons. The objective of this study is to assess the variations in physicochemical parameters of Sathnala Pond and determine their impact on water quality and aquatic life. Water samples were collected monthly from two sites in Sathnala Pond between February and July 2023, using sterilized bottles and maintaining stringent contamination controls. Key parameters such as temperature, pH, electrical conductivity, turbidity, hardness, alkalinity, chloride, nitrate, phosphate, dissolved oxygen, BOD, and COD were analyzed using standard methods. Statistical analysis was performed using Pearson’s correlation to identify relationships between parameters. Water temperature ranged from 22.8°C to 35.2°C, with pH values fluctuating between 7.5 and 9.1, indicating increased alkalinity in July. Dissolved oxygen levels were low in March and April, while COD consistently exceeded standard limits, highlighting significant organic and inorganic pollution. Other parameters remained within acceptable ranges, but seasonal variations and high COD levels suggest ongoing water quality concerns. The study reveals significant seasonal variations and persistent pollution issues in Sathnala Pond, underscoring the need for enhanced monitoring and management practices.